Comparative Analysis of Ribosomal Protein Gene, eL14 Expression between Two Types of Colorectal Carcinoma Cell Lines - Lau, Melinda Mei-Lin; Sim, Edmund U. H. (UNIMAS Publisher, 2020)
Association between the expression of ribosomal protein (RP) genes and cancer is widely known. More specifically, the extra-ribosomal functions of RPs have been linked to carcinogenesis. The ribosomal protein gene, eL14 has been reported to be associated with malignancy of the colorectum, albeit of mechanism yet unclear. Its expression in cells derived from different tissue origin of colorectal carcinoma (CRC) has never been explored. Therefore, this study aims to comparatively analyse the expression pattern of eL14 between two different CRC cell lines (DLD-1 and HCT116). It involved a conventional gene expression analysis, the Reverse-Transcriptase PCR (RT-PCR) assays. Products of RT-PCR assay were resolved via an agarose gel electrophoresis method, and band intensities of amplicons were documented and quantified using TotalLab Quant software. We observed differential expression patterns of eL14 between DLD-1 and HCT116 cells, but statistical analysis revealed insignificant differences. Therefore, the relevance of eL14 as a biomarker to distinguish between different colorectal cancer cells is suggestive but not conclusive.